The Ethanol Extract of Osmanthus fragrans Flowers Reduces Oxidative Stress and Allergic Airway Inflammation in an Animal Model. (10th December 2013) - Hung, Chien-Ya; Huang, Fu-Long; Shi, Li-Shian; Ka, Shuk-Man; Wang, Jing-Yao; Tsai, Yu-Cheng; Hung, Tsung-Jen; Ye, Yi-Ling
Abstract : The Osmanthus fragrans flower, a popular herb in Eastern countries, contains several antioxidant compounds. Ben Cao Gang Mu, traditional Chinese medical literature, describes the usefulness of these flowers for phlegm and stasis reduction, arrest of dysentery with blood in the bowel, and stomachache and diarrhea treatment. However, modern evidence regarding the therapeutic efficacy of these flowers is limited. This study was aimed at assessing the antioxidative effects of the ethanol extract of O. fragrans flowers (OFE) in vivo and evaluating its antioxidant maintenance and therapeutic effect on an allergic airway inflammation in mice. After OFE's oral administration to mice, the values obtained in the oxygen radical absorbance capacity assay as well as the glutathione concentration in the lungs and spleens of mice increased while thiobarbituric acid reactive substances decreased significantly, indicating OFE's significant in vivo antioxidant activity. OFE was also therapeutically efficacious in a mouse model of ovalbumin-induced allergic airway inflammation. Orally administered OFE suppressed ovalbumin-specific IgE production and inflammatory cell infiltration in the lung. Moreover, the antioxidative state of the mice improved. Thus, our findings confirm the ability of the O. fragrans flowers to reduce phlegm and suggest that OFE may be useful as an antiallergic agent.